Impact of evidence-based healthcare education for Chinese medicine practitioners: A pre-post evaluation. (August 2019) - Wong, Charlene H.L.; Wu, Irene X.Y.; Cheung, William K.W.; Ho, Robin S.T.; Leach, Matthew J.; Peng, Wenbo; Zhang, Yan; Wu, Justin C.Y.; Chung, Vincent C.H.
Highlights: Customized educational workshop effectively improves CMPs' attitudes and knowledge of EBHC. Customized educational workshop has limited effectiveness in altering CMPs' subjective norm on EBHC. CMPs never receive EBHC training showed greater improvement in attitude, decision making, and intention and behaviour domains. Implementation strategy should be tailored for promoting EBHC practice in Chinese medicine and in innovating clinical research methodology. Abstract: WHO Traditional Medicine Strategy 2014-23 recommended evidence-based healthcare (EBHC) education for traditional and complementary medicine (T&CM) professionals, including Chinese medicine practitioners (CMPs). We evaluated the impact of a customized educational workshop on Hong Kong CMPs' knowledge, attitude and practice of EBHC. Two validated instruments, Evidence-based Practice Questionnaire (EPQ) and Evidence-based Practice Inventory (EPI), were used to assess the impact of EBHC education. Paired t-tests were used to compare scores before and after the workshop. Multiple linear regression was performed to explore the associations between changes in EPQ/EPI scores and CMPs' characteristics. CMPs who completed the workshop (n = 59) demonstrated significant improvements in the attitude (p = 0.013) and knowledge domains of the EPQ (p = 0.005). Significant improvements were also observed in the attitude, perceived behavioural control, decision making, and intention and behaviour domains of the EPI. CMPs who had never received prior EBHC training showed a larger magnitude of improvement in the EPI attitude (p = 0.032), decision making (p = 0.015), and intention and behaviour (p = 0.015) domains post-workshop. Our findings suggest that tailored workshop is effective in strengthening knowledge and in improving attitudes towards EBHC. Future RCTs should be conducted to affirm our findings. Future initiatives may consider incorporating this education approach into CMP curricula, as well as facilitating implementation of EBHC in routine Chinese medicine practice.